IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI UPAYA UNTUK MENINGKATKAN CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY (STUDI KASUS PADA BSI KCP MALANG SOETTA) - Khotimah, Khusnul; Budianto, Eka Wahyu Hestya (Jurnal Riset Akuntansi Politala, 2024)
This study aims to determine the extent of the role of CRM in increasing customer satisfaction and loyalty in the long term for good sustainability, especially by applying existing Islamic values, especially in sharia-based banking such as BSI KCP Malang Soetta. The research conducted in 2024 is qualitative with a descriptive approach using primary and secondary data collected through library data, interview techniques, observation, and documentation. The data analysis process starts from the process of data collection, reduction, presentation and conclusion drawing to produce findings about what motivates the application of CRM such as relationships that are considered unique, the application of the pareto law, research 68% of customers leave due to poor service etc.. How the procedures for implementing CRM can be done with 3 strategies namely one off one marketing, partnering programs, and continuity marketing. Including the impact and obstacles that must be faced from the implementation of CRM.